1980
DOI: 10.1007/bf02932920
|View full text |Cite
|
Sign up to set email alerts
|

Structure of epicuticular waxes on spikes and leaf sheaths of barley as revealed by a direct platinum replica technique

Abstract: A direct platinum replica technique is described for studying cuticle surfaces with few or no projecting wax structures. It is furthermore demonstrated that the structure of some small plate waxes can be elucidated using negative staining.Three types of epicuticular waxes are present on barley cuticular surfaces: (i) long, thin tubes and 13-diketone lipids characterize that on the glumes, lemmas and uppermost leaf sheaths; (ii) highly lobed plates, large amounts of primary alcohols (predominantly C26) and an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1982
1982
1991
1991

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Two possibilities can be envisaged: either the ~-ketoacyl elongase system is involved in modifying the fas product(s) to ~-ketoacyl chains which are then elongated by the acyl elongase and/or the t~-ketoacyl elongase requires t3-ketoacyl chains as the initial substrate for elongation. While an acyl elongase must function in all barley epidermal cells, e.g., those of the leaf blades, the i~-ketoacyl elongase is restricted to given epidermal cells such as those of the spike lemmas, paieas and glumes (14) where it and the acyl elongase both function in the same cell.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two possibilities can be envisaged: either the ~-ketoacyl elongase system is involved in modifying the fas product(s) to ~-ketoacyl chains which are then elongated by the acyl elongase and/or the t~-ketoacyl elongase requires t3-ketoacyl chains as the initial substrate for elongation. While an acyl elongase must function in all barley epidermal cells, e.g., those of the leaf blades, the i~-ketoacyl elongase is restricted to given epidermal cells such as those of the spike lemmas, paieas and glumes (14) where it and the acyl elongase both function in the same cell.…”
Section: Discussionmentioning
confidence: 99%
“…All four investigated alleles at this locus determine waxes lacking I~-and hydroxy-[~-diketones and having relatively increased proportions of primary alcohols, making the latter one of the three prominent lipid classes. The primary alcohols, however, do not dominate the wax as they do that from leaf blades and the lower leaf sheaths and internodes (see 14). The distribution of Cer-yy spike lipid classes is most similar to that from wild type awns (14).…”
Section: Composition Of Waxes On Spikes Of Fourmentioning
confidence: 95%
See 1 more Smart Citation
“…The presence of filaments (or thin tubes) was assessed by us from the glumes alone (Part I of these studies), whereas presence of P-diketones was assessed from whole plants (Part 11). Simpson and von Wettstein-Knowles (1980) found that in Hordeum vulgare material long thin tubes and P-diketones characterize glumes, lemmas, and upper leaf sheaths. The correspondence between wax filaments and P-diketones is well established (Tulloch 1976;von Wettstein-Knowles 1972).…”
Section: What Is the Most Important Result?mentioning
confidence: 98%
“…Co-operating Danish and Swedish researchers have made this mutant type the probably best known character complex in any cultivated plant. Mutants have been isolated and gene localized by LUNDQVIST and VON WETTSTEIN (1962WETTSTEIN ( , et al 1968; their influence on yield has been studied at Svalof (GUSTAFSSON 1963); electron microscopy and biochemical analyses have been done by VON WETSTEIN and VON WETTSTEIN-KNOWLES (LUNDQVIST et al 1968; VON WETTSTEIN-KNOWLES 1971 WETTSTEIN-KNOWLES and NETTING 1976;SIMPSON and VON WETTSTEIN-KNOWLES 1980; WETTSTEIN-KNOWLES 1983); cer loci have been chromosome mapped by SBGAARD 1973SBGAARD , 1974SBGAARD , 1977a; and the reactions of cer mutants to various climates have been studied in the Stockholm phytotron by GUSTAFSSON et al (1975).…”
mentioning
confidence: 99%